Impaired peripheral vasoconstrictor response to orthostatic stress in patients with multiple system atrophy. Issue 8 (August 2015) - Suzuki, Junichiro; Nakamura, Tomohiko; Hirayama, Masaaki; Mizutani, Yasuaki; Okada, Akinori; Ito, Mizuki; Watanabe, Hirohisa; Sobue, Gen
Abstract: Background and purpose: Most patients with multiple system atrophy (MSA) develop autonomic dysfunction; however, orthostatic hypotension is not always present. Failure of the vasoconstrictor response is thought to be responsible for orthostatic hypotension, but the degree of impairment of this response in patients with MSA is unclear. We assessed autonomic function in patients with MSA by evaluating the vasoconstrictive response during a head-up tilt test and determining its relationship to orthostatic hypotension. As an additional examination, the efficacy of norepinephrine in treating orthostatic hypotension was also assessed. Methods: The study included 82 patients with MSA and 28 controls. Measures of total peripheral resistance were obtained during a head-up tilt test. Norepinephrine was administered to the patients lacking a vasoconstrictive response to evaluate its ability to treat orthostatic hypotension. Results: At a 60° tilt, orthostatic hypotension occurred in 47.6% of the patients and 0% of controls. Reduction in total peripheral resistance from baseline at a 60° tilt was observed in 69.5% of the patients and 0% of controls. In patients with MSA, changes in systolic blood pressure from the baseline at a 60° tilt correlated positively with changes in the total peripheral resistance (r = 0.69, p < 0.0001). Norepinephrine prevented the reduction of total peripheral resistance and development of orthostatic hypotension. Conclusions: A large number of patients with MSA with and without orthostatic hypotension have an impaired peripheral vasoconstrictive response, suggesting a high frequency of cardiovascular dysautonomia with an associated risk of developing orthostatic hypotension. A norepinephrine infusion was effective for treating orthostatic hypotension. Highlights: We examined the characteristic of cardiovascular dysautonomia in MSA patients. Orthostatic hypotension occurred in 47.6% of the patients. Impaired peripheral vasoconstriction was observed in 69.5% of the patients. Norepinephrine is effective for preventing the development orthostatic hypotension.